Interspecific shared collective decision-making in two forensically important species - Boulay, Julien (Proc Biol Sci, 2016)
To date, the study of collective behaviour has mainly focused on intraspecific situations: the collective decision-making of mixed-species groups involving interspecific aggregation–segregation has received little attention. Here, we show that, in both conspecific and heterospecific groups, the larvae of two species (Lucilia sericata and Calliphora vomitoria, calliphorid carrion-feeding flies) were able to make a collective choice. In all groups, the choice was made within a few minutes and persisted throughout the period of the experiment. The monitoring of a focal individual within a group showed that these aggregations were governed by attractive and retentive effects of the group. Furthermore, the similarity observed between the conspecific and heterospecific groups suggested the existence of shared aggregation signals. The group size was found to have a stronger influence than the species of necrophagous larvae. These results should be viewed in relation to the well-known correlation between group size and heat generation. This study provides the first experimental examination of the dynamics of collective decision-making in mixed-species groups of invertebrates, contributing to our understanding of the cooperation–competition phenomenon in animal social groups.